The Condition of Coral Reef Ecosystem for the Suitability of Dive Tourism Utilization in Karimunjawa Island, Karimunjawa National Park, Jepara - Joshua Owen Mangotang; Munasik; Ibnu Pratikto (Prospect Publishing, 2023)
Coral reef ecosystems are frequently used for underwater recreation due to their beauty which is useful as one of the marine tourism locations to promote tourism in the area. The purpose of this study was to determine the condition of the Karimunjawa Island coral reef ecosystem and its feasibility to be used as a dive site. This research entirely uses descriptive methods and purposive sampling to determine the location of coral reef ecosystem sampling locations. Determination of the suitability of coral reef ecosystems for diving tourism is done by using the index of suitability for diving tourism by Yulianda (2007). Based on the result obtained, the suitability of the coral reef ecosystem in Karimunjawa Island to be used as a diving site is most likely suitable. Each location shows a value that is sufficient for doing a diving tourism activities with an average value of 75.75% which is included in the very suitable category (S1).